Evaluasi Program Kecakapan Hidup Di Sumatera Utara (Studi Kasus Sanggar Kegiatan Batu Bara) - Umi Ningrum (Proceedings of Annual Conference on Islamic Educational Management, 2021)
In This research aims to evaluate: (1) long-term results of life proficiency programs, (2) Medium term results of life proficiency programs, (3) results of a live proficiency program, (4) The process of life proficiency programs, (5) input of life proficiency programs in the SKB coal. This research is a type of evaluation study that refers to the concept of Logical Framework Models. The results of this research show: (1) The long-term results of bridal makeup courses and computers have been achieved according to criteria but not on sewing courses. (2) The medium-term results of the bridal makeup course and the computer have been accomplished according to success criteria but not on the sewing course. (3) The result of the bride and computer makeup course has been achieved according to success criteria but not on sewing course. (4) The process has not been fully implemented optimally, namely the socialization of activities using Internet media is not optimal as well as monitoring and evaluation activities have not been conducted thoroughly. Monitoring and evaluation is limited only to the evaluation of the learning, and does not include monitoring and evaluation on the level of the program (5) Inputs have not fully supported the implementation of activities, especially related to the problem of provision of and funding activities. Keywords: Program Evaluation, Life Skill, Coal Workshop.